Surat Keputusan Tata Usaha Negara yang bersifat Fiktif Positif - Utama, Kartika Widya (Magister Kenotariatan Universitas Diponegoro, 2015)
Abstract Government Administration Act has changed the public paradigm regarding the decree of the state administration which contains a grant or denial of an application for state administration. The granting of an administration application, now is a positive fictitious state. This article will discuss about what is the meaning of an administrative decision that are fictitious positive and it legal consequences by using legal research , reviewing rules related law . The advice from the author is there is a necessity to improve the standard of service from the official / State Administrative Agency in addressing the provisions on the Government Administration Act. Keywords: Decree, Administration, Fictive Positive Abstrak Undang-Undang Administrasi Pemerintahan telah merubah paradigma umum mengenai surat keputusan tata usaha negara, yang berisi suatu pengkabulan atau penolakan permohonan administrasi negara. Pengkabulan permohonan kini dapat bersifat fiktif positif. Artikel ini akan membahas mengenai apa yang dimaksud dengan Keputusan Tata Usaha Negara yang bersifat fiktif positif dan akibat hukumnya dengan menggunakan metode legal research, yaitu dengan mengkaji aturan-aturan hukum yang terkait. Saran yang diajukan adalah perlu peningkatan standar pelayanan dari Pejabat / Badan Tata Usaha Negara dalam menyikapi ketentuan dalam Undang-Undang Administrasi Pemerintahan Tersebut. Kata kunci: Surat Keputusan, Administrasi Negara, Fiktif Positif